2015
DOI: 10.1097/iae.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retina Capillary Invasion and Ellipsoid Zone Loss in Macular Telangiectasia Type 2 Imaged by Optical Coherence Tomography Angiography

Abstract: Optical coherence tomography angiography shows capillary proliferation in the outer retina corresponding to areas of EZ loss, which could be a useful marker to monitor the efficacy of possible treatments in MacTel2 disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…In addition, we found that there was a strong correlation between the area of outer retina capillary proliferation and the area of EZ loss. This builds on previous findings described qualitatively by Gaudric et al, 18 which noted that “deep retinal capillaries invaded the outer retina specifically in the area of EZ loss.”…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In addition, we found that there was a strong correlation between the area of outer retina capillary proliferation and the area of EZ loss. This builds on previous findings described qualitatively by Gaudric et al, 18 which noted that “deep retinal capillaries invaded the outer retina specifically in the area of EZ loss.”…”
Section: Discussionsupporting
confidence: 88%
“…1417,23 Other studies have measured the en face total area of the EZ disruption, or have reported on the co-localization of area of EZ breakdown and proliferation of abnormal capillary vessels. 10,11,13,18 Our study adds to the current knowledge of EZ disruption in MacTel type 2 by investigating EZ mapping technology for quantifying EZ breakdown. 20 First, we found that EZ-RPE thickness, area, and volume measurements in eyes with MacTel type 2 were significantly decreased when compared to age- and sex-matched normative controls, and percentage of EZ atrophy and attenuation were significantly increased when compared to normative controls (Table 3).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations